1994
DOI: 10.1139/o94-083
|View full text |Cite
|
Sign up to set email alerts
|

DNA cleavage in rat liver nuclei activated by Mg2+ or Ca2+ + Mg2+ is inhibited by a variety of structurally unrelated inhibitors

Abstract: Internucleosomal DNA fragmentation is often regarded as the biochemical hallmark of apoptosis and can be reproduced in vitro in rat liver nuclei. In this study we demonstrate that DNA is initially cleaved into > or = 700, 200-250, and 30-50 kilobase pair (kbp) fragments via a Mg(2+)-dependent, multistep process which can be potentiated by Ca2+. The subsequent internucleosomal cleavage requires both Ca2+ and Mg2+. Furthermore, we show that the heavy metals Cd2+ and Hg2+, dichloroisocoumarin (a general serine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Similar effects have been described earlier (45)(46)(47)(48), although the protective effects of TPCK, DCI, or LLnL on cell survival noted in these studies were attributed to inhibition of an unidentified serine protease or of calpain. These observations seem at first glance to be contradictory to previous results (14) and to the findings reported here, but they can be explained on the basis of cell-specific differences in cell cycle regulation and the proliferative status of the cell, as manifested, for instance, by the expression of c-Myc.…”
supporting
confidence: 85%
“…Similar effects have been described earlier (45)(46)(47)(48), although the protective effects of TPCK, DCI, or LLnL on cell survival noted in these studies were attributed to inhibition of an unidentified serine protease or of calpain. These observations seem at first glance to be contradictory to previous results (14) and to the findings reported here, but they can be explained on the basis of cell-specific differences in cell cycle regulation and the proliferative status of the cell, as manifested, for instance, by the expression of c-Myc.…”
supporting
confidence: 85%
“…Ca 2+ is one of the most significant intracellular messengers in modulating cell growth and differentiation, and plays an essential role in the induction of apoptosis. However, the role of Ca 2+ as an intracellular messenger is incomplete without the coexistence of internal Mg 2+ ions (33). Consistent with the above implication, the experiment showed that SeMoV markedly increased intracellular Ca 2+ and Mg 2+ concentrations.…”
Section: Discussionsupporting
confidence: 80%
“…Ca 2+ and Mg 2+ play a crucial role in governing the morphological and biochemical changes attributed to apoptotic cell death (33). Therefore, the perturbations of intracellular ion homeostasis, pH value and MMP may be a conspicuous manifestation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, we and others (29), have shown caspase-11 is not expressed in caspase-1-deficient mice and, although caspase-12 is expressed, we found no evidence that it is up-regulated, at least at the mRNA level. Alternatively, neutrophil apoptosis may be initiated independently of upstream caspases, perhaps via mitochondrial factors (35) or involvement of serine proteases (9,36).…”
Section: Discussionmentioning
confidence: 99%